Meningkatkan Jumlah Nasabah Dalam Masa Pandemi Covid-19 ditinjau dari Peran Pegawai pada KSP Nusa Abadi - Riana Dewi Kartika (Sekolah Tinggi Ilmu Ekonomi Satya Dharma, 2021)
The purpose of this study was to find out how the role of employees in increasing the number of customers during the Covid-1 Pandemic at KSP Nusa Abadi. This study used a qualitative approach. The data collection technique used in this research is the method of documentation, and structured interviews where the interview instrument uses a purposive systematic sampling technique. The people selected as informants were the leaders of KSP Nusa Abadi, KSP Nusa Abadi staff and members of KSP Nusa Abadi. The number of selected informants is 5 people. Data analysis techniques used in this research are data collection, data reduction, data presentation and verification. The results of this study are that KSP Nusa Abadi employees have played a role in carrying out their duties and responsibilities. Employees serve customers well, namely directly reviewing customers and prospective customers through humantouch and face to face approaches. Apart from offering various programs to customers and prospective customers, KSP employees also build relationships between customers based on the principle of kinship. In order to increase the number of customers during the COVID-19 pandemic, KSP employees should think about the latest ways with technological developments. Balancing between the two methods, namely the Humantouch and Highttech approaches.